PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING TERINTEGRASI SAINS TERHADAP MOTIVASI BELAJAR FIQIH DI MADRASAH IBTIDIAYAH - Nadhiroh, Yulsiva Anissatun; Soraya, Irma; Hamdani, Asep Saepul (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2024)
it because this science studies about sharia, siyasah, mamalah, ubudiyah, akhwal syaksiyah. Moreover, in matters of worship such as prayer, teachers should be able to correlate this with science. So that students can understand it completely by using their reason and faith in learning something. In the implementation of learning in the classroom, it was found that the value of the learning outcomes of Fiqh in class III decreased. Therefore, the teacher used a snowball throwing model of learning integrated with science to improve the learning outcomes of Fiqh in class III MI Hidayatullah, Blitar City. This study uses a quantitative method with descriptive data analysis and the Wilcoxon test. The results of this study were that 22 students out of 25 students in class III experienced an increase in their scores on the post-test. While the other 3 students still got the same score during the post-test. The average result of the fiqh score before being given treatment with the science-integrated snowball throwing method was 58.40 while the average score after being given treatment was 84.20. In the average section, the increase in the score was 11.50 and the number of positive rankings (Sum Ranks) was 253.00.